2022
DOI: 10.1101/2022.02.22.22271376
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of key meteorological parameters on the spread of COVID-19 in Mumbai: Correlation and Regression Analysis

Abstract: Purpose: To understand key meteorological parameters that influence the spread of COVID-19 in Mumbai, India (based on data from April 2020 - April 2021). Methods: The meteorological parameters chosen were Temperature, Dew Temperature, Humidity, Pressure, Wind Speed. The underlying basic relationships between meteorological parameters and COVID-19 information for Mumbai was understood using Spearman's rank correlation coefficients. After establishing basic relationships, Linear analysis and Generalized Additive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…While almost all recent studies focus on the direct analysis, the indirect effect is certainly relevant and whose importance should be quantified. In this context, it has been suggested that specific meteorological variables may play a role in the spread of the coronavirus in some countries Wang et al (2020b); Alvarez-Ramirez and Meraz (2020); Bannister-Tyrrell et al (2020); Bukhari and Jameel (2020); Ma et al (2020); Sajadi et al (2020); Wang et al (2020a); Araujo and Naimi (2020); Carleton and Meng (2020); Ficetola and Rubolini (2020); Islam et al (2021);Loché Fernández-Ahúja and Fernández Martínez (2021); Chelani and Gautam (2022); Shetty et al (2022); Souza Júnior et al (2022); Briz-Redón and Serrano-Aroca (2020); Ogunjo et al (2022); Damette et al (2021); Wei et al (2022), while others oppose to strong seasonal effects O'Reilly et al (2020); Jamil et al (2020). There are also proposals that several meteorological factors combined could describe the epidemic trend much better than single-factor models Chen et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…While almost all recent studies focus on the direct analysis, the indirect effect is certainly relevant and whose importance should be quantified. In this context, it has been suggested that specific meteorological variables may play a role in the spread of the coronavirus in some countries Wang et al (2020b); Alvarez-Ramirez and Meraz (2020); Bannister-Tyrrell et al (2020); Bukhari and Jameel (2020); Ma et al (2020); Sajadi et al (2020); Wang et al (2020a); Araujo and Naimi (2020); Carleton and Meng (2020); Ficetola and Rubolini (2020); Islam et al (2021);Loché Fernández-Ahúja and Fernández Martínez (2021); Chelani and Gautam (2022); Shetty et al (2022); Souza Júnior et al (2022); Briz-Redón and Serrano-Aroca (2020); Ogunjo et al (2022); Damette et al (2021); Wei et al (2022), while others oppose to strong seasonal effects O'Reilly et al (2020); Jamil et al (2020). There are also proposals that several meteorological factors combined could describe the epidemic trend much better than single-factor models Chen et al (2020).…”
Section: Introductionmentioning
confidence: 99%